RENEWABLE ENERGY STUDY THROUGH SOLAR POWER PLANTS FOR HOUSEHOLD WATER DISTRIBUTION SYSTEMS BASED ON STORAGE TANKS - Wiratno Y Sigin; Vontas Alfenny Nahan; Tarita Aprilani Sitinjak; Revianti Coenraad; Tuah; Danar Ariangga Windra Gautama; Frans Putra Ganesa; Adhevia Marissa (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
The availability of clean water is a basic need that must be met to ensure people's quality of life. The use of renewable energy, particularly through solar power plants (PLTS), offers an efficient and environmentally friendly solution. PLTS have the advantage of being an abundant energy source, being emission-free, and suitable for household applications in tropical regions like Indonesia, which experience high solar radiation intensity throughout the year (IEA, 2023; Mulyadi & Hartono, 2019). This research addresses the need for a solar-powered booster pump system integrated with a storage tank as a backup water source. The research was conducted in the Building Engineering Education Laboratory, Faculty of Teacher Training and Education, Palangka Raya University, designing a household water distribution system using a solar-powered booster pump integrated with a storage tank. Specific plans and targets include publication of this research in a SINTA-accredited journal, HKI, and a research video.